Challenges and Opportunities: A Qualitative Study of EFL Teachers' Digital Proficiency and its Impact on Interactive Language Assessment - Insani, Afra Nadya Putri; Aprilia, Putri Kurniawan; Mistar, Junaidi (VELES Voices of English Language Education Society, 2024)
This study investigates the digital proficiency of English as a Foreign Language (EFL) teachers concerning language assessment development. Employing a qualitative phenomenological approach, it explores the subjective experiences and perceptions of EFL teachers engaged in constructing language tests within educational contexts. Semi-structured interviews were conducted with three participants, each representing diverse backgrounds in English Language Teaching (ELT). Moreover, thematic analysis was utilized to interpret the collected data systematically. The findings reveal specific challenges encountered by teachers in implementing interactive language assessments, including the identification of appropriate instructional materials, selection of suitable assessment models, and integration of digital tools into teaching methodologies. Moreover, participants suggest that technology can positively impact student engagement, motivation, and collaboration during assessments. By recognizing the continuous nature of language learning and assessment, educators can better tailor their approaches to meet the evolving needs of language learners. This research contributes to the ongoing discourse on language assessment practices, highlighting the importance of incorporating digital resources and fostering a supportive learning environment for students.